Avaliação de genótipos de cártamo quanto ao desempenho agronômico, divergência genética e produtividade da água - Zoz, Tiago [UNESP] (2015)
The concept water productivity in agriculture is the relation between the yield of crop and the water quantity required to get that yield. Water is a valuable resource for agriculture; therefore, it is interesting to adopt crops with higher yield capacity and requires lower water quantity. Safflower (Carthamus tinctorius L.) is an oil crop that is getting highlight in last years, mainly due its high oil content of high quality and drought tolerance. However, safflower is an underexplored commercially crop in Brazil and due it, there are few studies about plant breeding and drought tolerance. This study aim to evaluate the agronomic performance, water productivity and the genetic divergence in safflower cultivars imported from United States in crop conditions of Brazil. In addition, this study aim to evaluate the water productivity of high oleic safflower genotypes under different water depth. The study was composed by two trials. The first trial, related to agronomic performance and genetic divergence of American cultivars in crop conditions of Brazil was run in Sao Manuel, SP, from April to September of 2012. The experimental design was randomized blocks with four replications. It were evaluated 12 safflower cultivars imported from United States. From the data of grain and oil yield it was estimated the water productivity in relation to grain and oil. It were estimated the genetic correlation coefficients, and from them, it were estimated the direct and indirect effects of traits evaluated on grain yield and oil yield by path analysis. The genetic divergence analysis between cultivars was performed by multivariate analysis technique of principal components analysis (PCA). The second trial, related to water productivity of high oleic safflower genotypes under different water depth was run in Lubbock - TX, United States, from May to October of 2013. The experimental design was randomized blocks with ...